Active biogeochemical cycles during the Marinoan global glaciation. (15th March 2022) - Ma, Haoran; Shen, Bing; Lang, Xianguo; Peng, Yongbo; Huang, Kangjun; Huang, Tianzheng; Fu, Yong; Tang, Wenbo
Abstract: Termination of the Marinoan global glaciation (650–635 million years ago, Ma) was immediately followed by the diversification of eukaryotes and possible occurrence of animals, suggesting the potential linkage between biological evolution and global glaciation. It is proposed that the post-glacial eukaryote evolution might have been triggered by environmental stress imposed by the extreme pan-glacial condition. However, how life survived through the global glaciation remains speculative. Neither is known about the habitability when the ocean was completely or mostly frozen. In this study, we explore the marine carbon and sulfur biogeochemical cycles during the Nantuo (Marinoan) glaciation (650–635 Ma) in South China. Both organic carbon (δ 13 Corg ) and pyrite sulfur isotopes (δ 34 Spy ) show significant stratigraphic variations, suggesting active biogeochemical cycles in the pan-glacial condition. By coupling both δ 13 Corg and δ 34 Spy data, we develop numerical models to constrain marine productivity and redox conditions during the Nantuo glaciation. The marine primary productivity showed a sharp decline in the onset of glaciation and recovered right before the cap carbonate precipitation. An episodic recovery of primary productivity was observed in the non-glacial interval between the two glacial episodes. In contrast, the marine productivity was still suppressed in initial deglaciation, during which the continental weathering was intense, presumably indicating high atmospheric CO2 level and low seawater pH value. The final recovery of marine primary productivity occurred in the topmost of Nantuo Formation, when the weathering intensity was already low. Therefore, the active biogeochemical cycle implies a sustained habitability, warranting the survivorship in the pan-glacial ocean, while the persistently low and delayed recovery of marine productivity might have imposed environmental stress for tens of million years, paving the way for the evolution of animals.